Management of Violent Behavior in Patients with Mental Disorders through a Psychiatric Nursing Approach: A Systematic Review - Dewi Kusumaningrum, Raden Roro; Kristiani Hutapea, Elpriede; Amarani, Anisa; Muhammad Fadly; Melky Sedeq Norman Ronaldo; Yuli Hidayati; Supriadi; Imran; Suriadi Jais (Lembaga Teewan Journal Solutions, 2026)
Background: Violent behavior is a common problem among patients with mental disorders and may endanger the patient, other people, and the surrounding environment. It is influenced by emotional disturbances, hallucinations, delusions, psychosocial stress, medication nonadherence, and limited family support. This systematic review aimed to identify violent behavior management strategies for patients with mental disorders through psychiatric nursing approaches based on evidence-based practice. Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Literature was searched in Google Scholar, PubMed, ScienceDirect, and ProQuest using the keywords “violent behavior”, “aggression”, “psychiatric nursing”, “mental disorder”, and “nursing intervention”. Eligible full-text articles in Indonesian or English were published between 2020 and 2025. Results: Effective psychiatric nursing approaches included therapeutic communication, de-escalation techniques, group activity therapy, cognitive behavioral therapy, relaxation therapy, spiritual approaches, and family support. These interventions helped patients recognize anger warning signs, improve emotional control, reduce aggressiveness, and prevent recurrence. Conclusion: A holistic and continuous psychiatric nursing approach is effective for managing violent behavior and supporting rehabilitation and recovery.